2004
DOI: 10.1103/physrevd.70.074511
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of monopoles and flux tubes in two-flavor dynamical QCD

Abstract: We investigate the confining properties of the QCD vacuum with N f 2 flavors of dynamical quarks, and compare the results with the properties of the quenched theory. We use nonperturbatively Oa improved Wilson fermions to keep cutoff effects small. We focus on color magnetic monopoles. Among the quantities we study are the monopole density and the monopole screening length, the static potential and the profile of the color electric flux tube. We furthermore derive the low-energy effective monopole action. Mark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 72 publications
11
52
1
Order By: Relevance
“…For the results of numerical simulations for SU(3) Yang-Mills theory in the MA gauge, see e.g., [89,90,91,92,93,94,95,96]. However, we do not necessarily need to consider the maximal breaking SU(N) → U(1) N −1 , although the maximal torus group is desirable as a gauge group of the low-energy effective Abelian gauge theory [53].…”
Section: Abelian Dominance and Magnetic Monopole Dominancementioning
confidence: 99%
See 2 more Smart Citations
“…For the results of numerical simulations for SU(3) Yang-Mills theory in the MA gauge, see e.g., [89,90,91,92,93,94,95,96]. However, we do not necessarily need to consider the maximal breaking SU(N) → U(1) N −1 , although the maximal torus group is desirable as a gauge group of the low-energy effective Abelian gauge theory [53].…”
Section: Abelian Dominance and Magnetic Monopole Dominancementioning
confidence: 99%
“…93 iii) The covariant derivative D (ǫ) µ [V ] obeys the correct transformation property, i.e., the adjoint rotation on a lattice: 14) provided that the link variable V x,µ transforms in the same way as the original link variable U x,µ :…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To check that the monopoles are successfully added, we detect the monopoles in the configurations. It has been found that the monopoles are divided in two clusters [15,14,5,17] in MA gauge. The small (ultraviolet) clusters are composed of the short monopole loops.…”
Section: Zero Modes Of Overlap Fermions Instantons and Monopoles Mamentioning
confidence: 99%
“…The monopole creation operator is defined in [2,3,4]. (4) Measuring the additional monopoles We check whether the pair of monopoles is successfully added in the configurations or not, by use of the method developed in [5]. We find that adding one monopole-antimonopole pair makes one long monopole loop in configurations.…”
Section: (3) Additional Monopolesmentioning
confidence: 99%